Classical Modern Dialectics: The Historical Development of the Science of Semantics in Arabic ‎Linguistics - Gita Febriyani; Hanomi (Al Ibrah: Journal of Arabic Language Education, 2025)
This research examines the historical development of the science of semantics in Arabic linguistics through a classical-modern dialectical approach. The study stems from the significance of this discipline as both a linguistic analysis tool and a medium for understanding the religio-cultural values of Arabic texts, rooted since the pre-Islamic era. Its primary objective is to trace the transformation of dilalah theory and methodology from the classical to the contemporary period, while exploring how semantic concepts have evolved across different intellectual and cultural contexts. Using a qualitative method based on comprehensive library research, the analysis focuses on the contributions of key thinkers such as Abu Al-Aswad Ad-Du'ali, Sibawayh, and Al-Jurjani (classical) as well as Ferdinand de Saussure, Noam Chomsky, Ibrahim Anis, and Tammam Hassan (modern). The findings confirm the consolidation of three main paradigms: referential, structural, and cognitive, reflecting the discipline's remarkable adaptation to linguistic challenges throughout history while affirming the continuous integration between Arabic linguistic heritage and modern theoretical frameworks. This synthesis demonstrates how traditional Arabic semantic analysis remains relevant in contemporary linguistic discourse.